Pemberdayaan Literasi Digital di Desa Waringin Kurung, Cimanggu, Pandeglang - Andi Kurniawan; Andhika Octa Indarso; Windhiadi Yoga Sembada; Khairul Anwar (Indonesian Journal of Society Engagement, 2021)
Digital literacy is used to find, analyze, create, and transmit information and communication technology information. Based on the experience of several countries, the use of information technology has become one of the drivers of economic development, especially in rural areas and can encourage regional development. The use of ICT is considered effective in reducing community migration from rural to urban areas and improving the quality of government services through e-governance. Waringin Kurung Village is one of the isolated villages with a neighborhood located in the southern part of Banten Province, directly adjacent to the Ujung Kulon National Park area. This community service aims to improve the ability of village officials in utilizing digital literacy for the efficiency of the village service system, encouraging the dissemination of village information and village information. The method of implementing digital literacy development consists of three stages: a practice test by socializing the use of electronic mail (email), and understanding test through pretest and post-test on the use of Microsoft word applications, and case studies and problem-solving about information strategies. We conclude that higher education communities should involve more in developing digital literacy in rural villages. It will help rural communities use technology for their village administration and enhance public information management through the website and other digital channels.